2006
DOI: 10.1590/s1516-44462006000100003
|View full text |Cite
|
Sign up to set email alerts
|

How do experts recognize schizophrenia: the role of the disorganization symptom

Abstract: How do experts recognize schizophrenia: the role of the disorganization symptom Como os especialistas reconhecem a esquizofrenia: o papel do sintoma desorganização A b s t r a c t Objective: Research on clinical reasoning has been useful in developing expert systems. These tools are based on Artificial Intelligence techniques which assist the physician in the diagnosis of complex diseases. The development of these systems is based on a cognitive model extracted through the identification of the clinical reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Symptoms usually begin in late adolescence or early adulthood. 19,20 The clinical manifestations are variable, including perceptual alterations (hallucinations), form and content of thought (incoherent thought or with loosening of associations, delusion), disorganized speech, grossly disorganized or catatonic behavior, and "negative" symptoms (alogia, affective flattening, avolition, social isolation). Cognitive impairments mainly affecting intelligence, memory, language, executive functioning, and attention domains are also common.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms usually begin in late adolescence or early adulthood. 19,20 The clinical manifestations are variable, including perceptual alterations (hallucinations), form and content of thought (incoherent thought or with loosening of associations, delusion), disorganized speech, grossly disorganized or catatonic behavior, and "negative" symptoms (alogia, affective flattening, avolition, social isolation). Cognitive impairments mainly affecting intelligence, memory, language, executive functioning, and attention domains are also common.…”
mentioning
confidence: 99%
“…Cognitive impairments mainly affecting intelligence, memory, language, executive functioning, and attention domains are also common. 20,21 Over the past three decades, neurophysiological studies using different models for schizophrenia have identified several brain alterations. There are global impairments in cognition with altered executive functions (action planning, inhibition, cognitive flexibility monitoring, abstract reasoning), memory (difficulties in the semantic organization of the content of the memory and overcoat in verbal memory and visuospatial tasks), attention (difficulties intrusions control, in the divided and sustained attention, focus changing) and language (fluency but without alterations in vocabulary).…”
mentioning
confidence: 99%
“…Highlighting, and even giving an "epistemic priority" to this background (Berrios, 2011a(Berrios, , 2011b, allows us to answer some of the difficulties faced by research that does not warn, or minimizes this aspect of psychotherapeutic practice. Thus, for example, it is understable the difficulties encountered in studies that have sought to consider the diagnostic process as a mode of reasoning guided exclusively by theoretical or methodological criteria such as those of Garb (1996) and those of Razzouk et al (2006). Instead, the clarification of social aspects linked to therapy has shown that there are prominent elements of the psychotherapeutic process that distance it from the traditional categories, for example those of diagnostics (Krause, 2005), to give a relevant role to diverse clinical formulations elaborated to give an answer to the psychological problems or psychic conflicts that the psychotherapist treats.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that clinicians, at the time of making clinical judgments, on numerous occasions do not use structured or schematized criteria but proceed by recognition and identification of stereotyped characteristics of typical cases, which when compared with the degree of "representativeness" that a particular case presents offers the therapist a more efficient way to reach a clinical judgment (Berrios & Marková, 2015;Garb, 1996). In another similar study (Razzouk, Mari, Shirakawa, Wainer, & Sigulem, 2006), it was intended to explain how experts recognize schizophrenia, under the assumption that a common pattern that could guide the diagnostic process could be found among professionals. However, they found that although psychotherapists coincided in the diagnosis of the same case, the process to achieve it was different in each one.…”
mentioning
confidence: 99%
“…Psychiatrists are experts and acquire their expert position through knowledge, clinical practice, personal skills and technical information (Razzouk, Mari, Shirakawa, Wainer, & Sigulem, 2006). According to Norman (2005) an expert has superior knowledge, formal and informal that is used in determining the solution to a particular problem as well as the ability to organize knowledge.…”
mentioning
confidence: 99%